2021
DOI: 10.1039/d1ra02986j
|View full text |Cite
|
Sign up to set email alerts
|

Electrospun and co-electrospun biopolymer nanofibers for skin wounds on diabetic patients: an overview

Abstract: Wound healing treatment in diabetic patients worldwide represents around 2.1 trillion dollars to global health sectors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 84 publications
0
10
0
Order By: Relevance
“…[11][12][13][14][15][16][17] These aspects highlight the immense need for a therapeutic dressing material possessing multifaceted properties. [18][19][20] A plethora of literature is available on wound-care materials based on the intended application, such as antimicrobial, debridement, absorbent, or occlusive. [21] Recently, substantial importance has been given to dressing materials that mimic the function of the extracellular matrix, which facilitates the migration and proliferation of dermal and epidermal cells for effective wound closure.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[11][12][13][14][15][16][17] These aspects highlight the immense need for a therapeutic dressing material possessing multifaceted properties. [18][19][20] A plethora of literature is available on wound-care materials based on the intended application, such as antimicrobial, debridement, absorbent, or occlusive. [21] Recently, substantial importance has been given to dressing materials that mimic the function of the extracellular matrix, which facilitates the migration and proliferation of dermal and epidermal cells for effective wound closure.…”
Section: Introductionmentioning
confidence: 99%
“…[ 11–17 ] These aspects highlight the immense need for a therapeutic dressing material possessing multifaceted properties. [ 18–20 ]…”
Section: Introductionmentioning
confidence: 99%
“…All the membranes showed well-organized topological structures, with ellipsoidal-shaped nanopores, which were arranged with the major axis along the fiber direction. Co-electrospinning method, also known as coaxial electrospinning, is a method derived from electrospinning, the difference being that in the case of co-electrospinning, two needles are used instead of one needle, which makes it possible to obtain a core-shell nanofiber [ 122 ]. Al-Badani et al [ 123 ] reported a possible polycaprolactone/gelatin membrane as a tunable drug delivery system for bone tissue regeneration via co-electrospinning ( Figure 3 ).…”
Section: Biomedical Applications Of Membranesmentioning
confidence: 99%
“…Synthetic polymers have made great progress in the preparation of wound dressings alone, and they are commonly used as scaffolds for drug encapsulation and delivery, 70 but their inherent disadvantages limit their further development and application. For example, the nanofibers made from PVA have poor thermal stability and strength 71 ; the electrospinning nanofiber films made from PCL and PLA have high hydrophobicity and lack of cell binding sites, 72 which limit their application in wound dressings. Meanwhile, synthetic polymer nanofibers achieve structural programming, but they lack the necessary biological functions, such as biocompatibility and low cytotoxicity.…”
Section: Electrospinning Wound Dressing Of Synthetic Polymersmentioning
confidence: 99%